Zatoichi meets Yojimbo [videorecording (DVD)] / / Zatōichi to yōjinbō The Toho Company and Katsu Productions present ; produced by Katsu Shintaro and Nishioka Hiroyoshi ; screenplay, Okamoto Kihachi and Yoshida Tetsuro ; directed by Okamoto Kihachi. - Okamoto, Kihachi, 1924-2005; Katsu, Shintarō, 1931-1997; Wakao, Ayako, 1933-; Mifune, Toshiro, 1920-1997; Shimozawa, Kan, 1892-1968 (AnimEigo, 2003)
The twentieth of a series of films set in medieval Japan about Ichi, a blind masseur who lives by the Yakuza code and uses his deadly cane sword against his enemies. In this episode, Zatoichi finds that one of his favorite villages has fallen prey to Boss Masagoro, the son of a merchant rumored to have stolen gold from the shogunate.